Nota dos editores - Santos, Raimundo Nonato Silva; Guarines, Deborah Cavalcante de Oliveira Salomão; Machado, Raquel Cavalcanti Ramos (Suffragium - Revista Científica do Tribunal Regional Eleitoral do Ceará, 2025)
Nota dos editores